Tingkat Kepatuhan Minum Obat Pasien Hipertensi di Klinik BMCI Malang - Aldesra Fitri; Beta Herilla Sekti; Intan Riyanti (LPPMKI - AKAFARMA AKFAR PIM, 2023)
High blood pressure, also known as hypertension, is a disease that is not contagious and seems to High blood pressure, also known as hypertension, is a disease that is not contagious and has been increasing in Indonesia over the years. It is a significant cause of illness and death, particularly in relation to stroke, along with smoking and a history of heart disease. In fact, up to 70% of stroke patients have hypertension. In Malang City, hypertension is one of the most prevalent diseases, with a total of 35,641 cases. The key to effective hypertension management is ensuring compliance with antihypertensive medication, which is primarily done at First Level Health Facilities (FKTP). Therefore, this study aimed to evaluate compliance levels among hypertensive patients who are registered with the Chronic Disease Management Program (PROLANIS) at the BMCI Malang Clinic. A descriptive cross-sectional method was used, and medication adherence questionnaires were administered using the Morisky Medication Adherence Scale (MMAS-8). The study found that 60% of hypertensive patients were between the ages of 56 and 65, 60% were female, and 64% had a low level of education. Based on their characteristics, more than half of the respondents had a moderate level of compliance.